1995
DOI: 10.1144/gsl.sp.1995.088.01.16
|View full text |Cite
|
Sign up to set email alerts
|

Late Jurassic-Early Cretaceous inversion of the northern East Shetland Basin, northern North Sea

Abstract: Current research into the structural evolution of the East Shetland Basin, northern North Sea, indicates that a significant phase of structural inversion occurred during the Latest Jurassic-Early Cretaceous.Structural effects of this tectonic phase include the pronounced uplift of pre-and syn-rift sequences along the western margin of the basin and the partial inversion of Mesozoic half-graben along intra-basinal NE-SW controlling faults. In addition, the localized occurrence of flower geometries and pop-ups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 30 publications
3
59
1
Order By: Relevance
“…However, debates exist on the significance of the reactivation of first-phase faults and its influence on the fault growth during the second rift phase (Lee and Hwang, 1993;Thomas and Coward, 1995;. Some authors utilizing high-quality 3D seismic reflection data in the East Shetland Basin in the northern North Sea argued that Triassic faults were largely crosscut and offset by oppositely dipping middle-late Jurassic faults, forming two generations of fault blocks tilted in opposite direction (Faerseth et al, 1997;Faerseth and Ravnas, 1998;.…”
Section: Analysis Of Subsurface and Field Datamentioning
confidence: 99%
“…However, debates exist on the significance of the reactivation of first-phase faults and its influence on the fault growth during the second rift phase (Lee and Hwang, 1993;Thomas and Coward, 1995;. Some authors utilizing high-quality 3D seismic reflection data in the East Shetland Basin in the northern North Sea argued that Triassic faults were largely crosscut and offset by oppositely dipping middle-late Jurassic faults, forming two generations of fault blocks tilted in opposite direction (Faerseth et al, 1997;Faerseth and Ravnas, 1998;.…”
Section: Analysis Of Subsurface and Field Datamentioning
confidence: 99%
“…The phenomenon of basin inversion has been documented worldwide. For example, mild to moderate inversion in intraplate basins has been observed in numerous North Atlantic basins (Cartwright, 1989;Chapman, 1989;Hayward & Graham, 1989;Roberts et al, 1993;Sinclair, 1995;Thomas & Coward, 1995) or in the North German Basin (Kossow et al, 2000;Kossow & Krawczyk, 2002;Gemmer et al, 2003). In addition, strongly shortened half grabens have been documented in the Alps (Gillcrist et al, 1987), with prominent examples found in the Central Andes (Kley & Monaldi, 2002) and Atlas mountains (Beauchamp et al, 1999;Teixell et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although inversion tectonics have been mainly studied in extensional and compressional fault systems using models (Bally, 1984;Williams et al, 1989) and field examples (Gillcrist et al, 1987;Kelly et al, 1999), research into oblique-slip structures (e.g. Casas-Sainz, 1993;Sinclair, 1995;Thomas and Coward, 1995;Quintana et al, 2004) is more scarce. The inversion and reactivation of transfer faults have been studied in sedimentary basins mainly on the basis of geophysical data (e.g.…”
Section: Introductionmentioning
confidence: 99%